BANK SPECIFIC DETERMINANTS OF LIQUIDITY IN JOINT VENTURE COMMERCIAL BANKS OF NEPAL FROM 2016/2017 TO 2020/2021 - Sharma, Bijay (JURNAL AKUNTANSI DAN AUDITING, 2023)
This study focuses on Bank Specific Determinants of Liquidity in Joint Venture Commercial Banks of Nepal from 2016/2017 to 2020/2021. Liquid Assets to Total Assets Ratio, Liquid Assets to Total Deposit Ratio and Quick Ratio are considered as dependent variable in this study. The independent variables used in this study are Capital Adequacy Ratio, Non-Performing Loan, Return on Assets and Bank Size.This research has used the simple random method of sampling and considered 3 joint venture commercial banks for the sample size from the total population of 7 banks. Secondary sources of data have been used from annual reports of the sample joint venture banks. The research study has used regression models and descriptive and analytical research design to test the significance of bank specific determinants of liquidity of sample banks.Liquid Assets to Total Deposit Ratio is found to be positively correlated with Capital Adequacy Ratio and negatively correlated with other independent variables used in this study such as Non-Performing Loan, Return on Assets and Bank Size. Liquid Assets to Total Assets Ratio is positively correlated with Capital Adequacy Ratio and negatively correlated with other independent variables used in this study such as Non-Performing Loan, Return on Assets and Bank Size. Quick Ratio is positively correlat4ed with Return on Assets and Capital Adequacy Ratio and negatively correlated with Non-Performing Loan and Bank Size. The regression coefficients of Capital Adequacy Ratio and Bank Size is positive whereas, the regression coefficients of Non-Performing Loan and Return on Assets is negative.